The Influences of Conversation Program at Madrasah Aliyah Babul Huda Tualang Cut in improving The Students’ Speaking Skill - Maulia, Wirda (JL3T (Journal of Linguistics, Literature and Language Teaching), 2021)
This study aimed to determine the influence of a conversation program in improving students’ speaking skills at Islamic Boarding School Babul Huda. The qualitative method was used in this research by using three techniques; observation, questionnaires, and interview in data collecting. The observation was used in order to get information directly about the space, actor, activity, object, act, event, time, goal, and feeling of the population. The questionnaires were used to gain more valid and reliable data about the students’ responses to the conversation program. At the same time, the interview was used to investigate whether the conversation program influences and improves the students’ speaking skills. The population of this study was only female of the students at MA Babul Huda. Thirty students were taken as the sample of the study. The result showed that the conversation program improved the students’ speaking skill based on the data obtained. The conversation program influenced the students’ speaking skills in communicating and interacting with one another; moreover, the students explained that they could present and share their ideas among the groups after the speaking activity.